A Critical Review of Mobile Learning: Phoenix, Fossil, Zombie or .....? - John Traxler (MDPI AG, 2021)
The established mobile learning paradigm is now two decades old; it grew out of the visions and resources of e-learning research communities in universities in the world's more economically developed regions. Whilst it has clearly been able to demonstrate many practical, pedagogic and conceptual achievements, it is now running out of steam. It has failed to adapt to a world where mobile technologies are pervasive, ubiquitous and intrusive and where people and communities can now own their own learning. This paper looks at the evolution of the established mobile learning paradigm and explores the current global, demographic, social and technical environment in order to develop a new paradigm more suited to the changed and changing realities and priorities. This is mobile learning2.0. The paper looks at the axioms and values of this paradigm and its possible tools and techniques. The treatment is discursive and critical. The paper reimagines the concepts and practices of learning with mobiles. It embraces many significant themes at a high level, including inclusive and equitable education; learning theories and design; pedagogical frameworks and methodologies; digital and media literacies; social media and learning environments; online collaboration and communities; Informal and formal learning.